IMPACT OF SUCCESSFUL TREATMENT OF HCV ON GLYCEMIC CONTROL IN TYPE 2 DIABETES PATIENTS - Muhammad Saeed Akhter; Maqsood Ahmad; Muhammad Irfan; Mubarak Ali Anjum; Muhammad Wasif Baig; Hooria Amer (Journal of University Medical & Dental College, 2019)
OBJECTIVE: HCV infection is more common among adults with type 2 diabetes and possibly it can aﬀect the glycemic control in patients with diabetes. This study was conducted to ﬁnd whether eradication of CHC infection with direct acting antiviral (DAA) agents is associated with good glycemic control in patients with type 2 diabetes or otherwise. MATERIAL AND METHODS: Among 545 patients with diabetes who were treated with DAA (Interferon & Ribavirin free regimen) for chronic HCV infection, were included in the study. Changes in average (HbA1c) levels and use of ant diabetic medication 6 months before and after DAA treatment were compared between patients who achieved sustained virologic response (SVR) and those who did not achieve SVR. RESULTS: In patients with high base line HbA1c, the drop in HbA1c in reference to DAA treatment was greater in those who achieved SVR (1.99%) in comparison to those who did not (1.70%) (Adjusted mean diﬀerence 0.29, p=0.02). The doses of anti diabetic agents decreased more in subjects who achieved SVR in comparison to those who met treatment failure. This was evident for those who were using Insulin for control of their diabetes, which dropped signiﬁcantly from 46.4% to 41.3% in patients achieving SVR compared with a slight increase from 48.7% to 50.2% in those who were in treatment failure group. CONCLUSION: It is hereby concluded that improved glycemic control is associated with eradication of HCV with DAA based regimens evidenced by decrease in mean HbA1c and decreased insulin as well as oral anti diabetic agents use in SVR achievers.